Hubungan Perilaku Penggunaan Alat Pelindung Diri (APD) dan Perilaku Personal Hygiene dengan Penyakit Kulit Menggunakan TRA (Theory of Reasoned Action) - Icha Rohmah Damayanti Agustin; Dewi Prihatini; Isa Ma’rufi (Pascasarjana Universitas Jember, 2020)
In order to prevent skin disease among worker, both Personal Protective Equipment (PPE) usage and hygiene personal play important role. The objective of this study is to analyse the correlation between PPE usage and hygiene personal toward skin disease among scavenger in TPA Pakusari – Jember. This study was observational analytics, with cross sectional design. The number of participants was 57 scavengers, consist of 36 female and 21 males. The statistical analysis used Cramer’s V by SPSS. The findings of this study is: 1) The PPE usage is correlated toward skin disease, 2) The hygiene personal is correlated toward skin disease. Keyword: skin disease, PPE utilising, hygiene personal